Exhibit credit panel draft - Unidentified author (Colorado State University. Libraries, 2009)
Draft of credit panel for Window to the World exhibit in spring 2009. Includes typed and handwritten notes.
Keywords: Fashion -- History; Fashion -- Exhibitions